Barley stripe mosaic virus-mediated somatic and heritable gene editing in barley (Hordeum vulgare L.) - Tamilselvan-Nattar-Amutha, Suriya; Hiekel, Stefan; Hartmann, Franziska; Lorenz, Jana; Dabhi, Riddhi Vijay; Dreissig, Steven; Hensel, Goetz; Kumlehn, Jochen; Heckmann, Stefan (Frontiers in Plant Science, 2023)
Genome editing strategies in barley (Hordeum vulgare L.) typically rely on Agrobacterium-mediated genetic transformation for the delivery of required genetic reagents involving tissue culture techniques. These approaches are genotype-dependent, time-consuming, and labor-intensive, which hampers rapid genome editing in barley. More recently, plant RNA viruses have been engineered to transiently express short guide RNAs facilitating CRISPR/Cas9-based targeted genome editing in plants that constitutively express Cas9. Here, we explored virus-induced genome editing (VIGE) based on barley stripe mosaic virus (BSMV) in Cas9-transgenic barley. Somatic and heritable editing in the ALBOSTRIANS gene (CMF7) resulting in albino/variegated chloroplast-defective barley mutants is shown. In addition, somatic editing in meiosis-related candidate genes in barley encoding ASY1 (an axis-localized HORMA domain protein), MUS81 (a DNA structure-selective endonuclease), and ZYP1 (a transverse filament protein of the synaptonemal complex) was achieved. Hence, the presented VIGE approach using BSMV enables rapid somatic and also heritable targeted gene editing in barley.